Diversity & Inclusion: Fitness for Work Through a Personalized Work Plan For Workers With Disabilities and Chronic Diseases According to the Iso 30415/2021 - Cristaudo, Alfonso; Guglielmi, Giovanni; Foddis, Rudy; Caldi, Fabrizio; Buselli, Rodolfo; Brilli, Cinzia; Coggiola, Maurizio; Ceccarelli, Gianluca; Saffioti, Giuseppe (La Medicina del Lavoro, 2023)
The recent standard ISO 30415-2021 - Human resources management - Diversity and inclusion -  was developed internationally within the technical committee ISO/TC 260 "Human resources management" (Working group WG 8 "Diversity and inclusion") and underlines the need for actions to create a work environment that is inclusive of diversity (e.g. in terms of health, gender, age, ethnicity, culture). Developing an inclusive work environment requires ongoing commitment and input from the entire organization regarding policies, processes, organizational practices, and individual behavior. As far as the role of occupational medicine is concerned, this direction can be supported by the correct management of disabled workers and workers with chronic pathologies that affect their fitness for duty. The "reasonable accommodation" is the way by which the European Union first, and the United Nations then intended to support the inclusion of disabled people in the world of work. The Personalized Work Plan includes different approaches (organizational, technical, procedural) meant for modifying the work activity envisaged for the disabled worker or for any worker suffering from chronic diseases or dysfunctions. The adoption of the Personalized Work Plan implies the effort of redesigning the workstation, the work procedures, or even the planning of different micro and macro tasks etc., in order to prioritize the adaptation of the working environment to the worker, safeguarding the value of the worker's productivity according to the principle of reasonable accommodation.